1995
DOI: 10.1148/radiology.197.1.7568837
|View full text |Cite
|
Sign up to set email alerts
|

Synovial fluid in the hindfoot and ankle: detection of amount and distribution with US.

Abstract: US of the hindfoot and ankle commonly depicts articular, bursal, and tendon sheath fluid in asymptomatic volunteers. The presence of fluid in these locations, even when unilateral or asymmetric, does not necessarily imply underlying abnormality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
34
0
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(41 citation statements)
references
References 0 publications
5
34
0
2
Order By: Relevance
“…It is a flexor of the great toe and assists in plantar flexion of the foot at the ankle. Several studies have confirmed that the FHL tendon sheath communicates with the ankle joint [3][4][5][6]. These have a proximal and distal component, which together make up the synovial sheath of the FHL tendon.…”
Section: Introductionmentioning
confidence: 92%
“…It is a flexor of the great toe and assists in plantar flexion of the foot at the ankle. Several studies have confirmed that the FHL tendon sheath communicates with the ankle joint [3][4][5][6]. These have a proximal and distal component, which together make up the synovial sheath of the FHL tendon.…”
Section: Introductionmentioning
confidence: 92%
“…Bei gesunden Probanden wurde Flüssigkeit nachgewiesen im MTP-Gelenk sagittal bis zu 3 mm (14), im OSG ventral, sagittal bis 3 mm (14, 21) und dorsal, sagittal bis 1 mm. Flüssigkeit wurde in der Bursa subachillea bis zu 2,5 mm gefunden (21). Um die Sehne des M. tibialis posterior wurde ein Flüssig-keitssaum von maximal 4 mm gefunden.…”
Section: Diskussionunclassified
“…Um die Sehne des M. tibialis posterior wurde ein Flüssig-keitssaum von maximal 4 mm gefunden. Die Peronaeussehnen hatten einen Saum bis 3 mm (21).…”
Section: Diskussionunclassified
“…[1][2][3][4][5][6][7][8] Ultrasonographic detection of differences in the thickness of synovial effusion in the knee joints of RA patients by scanning at different sites has not previously been clearly demonstrated. In the present study, we calculated the thickness of the synovial effusion layer at the lateral, superior, and medial aspects of the patella using the measurement scale on the ultrasonograph.…”
Section: Introductionmentioning
confidence: 99%